Residual vestibular function after vestibular schwannoma surgery - Černý, R; Balatková, Z; Hrubá, S; Danková, M; Volf, P; Kutílek, P; Plzák, J; Bandúrová, V; Koucký, V; Mrázková, E; Čada, Z (Neuro-Chirurgie, 2020)
OBJECTIVES: This study aimed to assess vestibular function in 39 patients who underwent neurectomy for vestibular schwannoma. METHOD: Semicircular canal reactivity was measured by video head-impulse test using high-frequency passive head acceleration. Response gain was calculated as a ratio between the areas under the eye-velocity curve and the head-velocity curve. STATISTICAL ANALYSIS: Student t-test was used for to compare quantitative variables. ANOVA was used to test inter-group differences in categoric variables. RESULTS: In all cases, surgery-side gain on head impulse test was low, with increased gain asymmetry. A subgroup of 7 patients (18%) showed relatively high gain in vestibulo-ocular reflex on the surgery side. Caloric reaction was absent in all cases. These findings indicate that residual vestibular function can be conserved following vestibular schwannoma extirpation. CONCLUSION: Cases with moderate vestibulo-ocular reflex gain were a subgroup with partial conservation of vestibular nerve fibers. Whether this is a predictor of better functional prognosis remains to be elucidated. Higher gain correlated with less extensive surgery and sparing of the inferior vestibular nerve. Low gain correlated with complete vestibular neurectomy. This information may guide rehabilitation strategy following surgery.
Keywords: vestibulární aparát; senioři; Reflex, Vestibulo-Ocular; Head Impulse Test; Vestibular Function Tests; pooperační období; Postoperative Period; Prognosis; Middle Aged; mužské pohlaví; pulsní rotační test; Adult; neurochirurgické výkony; Neuroma, Acoustic; Postoperative Complications; Vestibule, Labyrinth; ženské pohlaví; prognóza; Humans; Neurectomy; vestibulární schwannom; Head-impulse test; lidé středního věku; nervová vlákna; vestibulookulární reflex; vestibulární funkční testy; dospělí; Nerve Fibers; Neurosurgical Procedures; Female; Aged; Vestibulo-ocular reflex; pooperační komplikace; Vestibular schwannoma; lidé; Male